The effect of aromatherapy intervention with Bergamot and Grapefruit essential oils on premenstrual syndrome and menstrual symptoms: a randomized controlled trial - Esra Özer; Şerife İrem Döner; Hafize Dağ Tüzmen (BMC Complementary Medicine and Therapies)
Abstract Background Premenstrual syndrome and menstrual symptoms adversely affect approximately 80–95% of women of reproductive age. Aromatherapy interventions are used to reduce premenstrual syndrome and menstrual symptoms. This study was conducted to determine the effect of aromatherapy intervention with bergamot and grapefruit essential oils on premenstrual syndrome and menstrual symptoms. Methods Ninety women with premenstrual syndrome were included the study. Participants were randomly divided into 3 groups: Bergamot(n = 30), Grapefruit(n = 30), Placebo(n = 30). Participants in each group were made to smell pure essential oil for 30 min 3 times a day for 4 days during the luteal phase of the menstrual cycle. The used was repeated in 3 menstrual cycles. “Premenstrual Syndrome Scale (PMSS)” was used to evaluate premenstrual syndrome and “Menstrual Symptom Questionnaire (MSQ)” was used to evaluate menstrual symptoms. All measurements were performed before and after the study. Results The results showed that grapefruit essential oil was effective in reducing PMSS total score (p = 0.010) and sub-scale scores (depressive affect, anxiety, fatigue, depressive thoughts, appetite changes, sleep changes and bloating (p < 0.001), irritability (p = 0.024), pain (p = 0.047)). Although grapefruit essential oil had no effect on the total score of the MSQ. Grapefruit essential oil was found to be effective in reducing the MSQ scale sub-scale scores (menstrual pain symptoms (p = 0.024) and the use of coping methods with menstrual pain (p = 0.011)). Bergamot essential oil was found to be effective in reducing PMSS total score (p = 0.001) and PMSS sub-scale scores depressive affect (p = 0.013), irritability (p = 0.034), depressive thoughts and appetite changes (p = 0.026), pain (p = 0.001)). In addition, there was no effect on the menstrual syndrome scale and its sub-dimensions (p > 0.05). Conclusion Grapefruit essential oil was effective in reducing both premenstrual syndrome and menstrual symptoms, whereas bergamot essential oil was only effective in reducing premenstrual symptoms. Trial registration number NCT06289764 (2024-02-01).